2018
DOI: 10.1002/adfm.201707013
|View full text |Cite
|
Sign up to set email alerts
|

Microporous Polypyrrole‐Coated Graphene Foam for High‐Performance Multifunctional Sensors and Flexible Supercapacitors

Abstract: This study reports on the fabrication of pressure/temperature/strain sensors and all‐solid‐state flexible supercapacitors using only polydimethylsiloxane coated microporous polypyrrole/graphene foam composite (PDMS/PPy/GF) as a common material. A dual‐mode sensor is designed with PDMS/PPy/GF, which measures pressure and temperature with the changes of current and voltage, respectively, without interference to each other. The fabricated dual‐mode sensor shows high sensitivity, fast response/recovery, and high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(82 citation statements)
references
References 51 publications
2
78
0
Order By: Relevance
“…Synthesis of PPy was confirmed with FTIR (Fourier transform infrared) spectra, Raman spectroscopy, and X‐ray photoelectron spectroscopy (XPS) analysis. The FTIR data in Figure e confirms a peak at 1546 cm −1 associated with the antisymmetric ring stretching modes of PPy . The Raman peaks at 1339 and 1580 cm −1 in Figure f are associated with PPy ring stretching and CC backbone stretching of PPy, respectively .…”
Section: Resultsmentioning
confidence: 55%
“…Synthesis of PPy was confirmed with FTIR (Fourier transform infrared) spectra, Raman spectroscopy, and X‐ray photoelectron spectroscopy (XPS) analysis. The FTIR data in Figure e confirms a peak at 1546 cm −1 associated with the antisymmetric ring stretching modes of PPy . The Raman peaks at 1339 and 1580 cm −1 in Figure f are associated with PPy ring stretching and CC backbone stretching of PPy, respectively .…”
Section: Resultsmentioning
confidence: 55%
“…Polypyrrole (PPy) is also an environmentally stable and biocompatible ECP, with a high electrical conductivity in the range 40 S/cm to 50 S/cm [156,157], and with a mechanical flexibility and solubility that makes it easy to apply on fibre surfaces through bathing [158][159][160][161], electrodeposition [161], or in-situ polymerisation [70,157,[162][163][164]. PPy has been used as conductive coating on carbon fibres and PDMS-carbon fibre bundles via electropolymerisation to create a fibre-based e-skin capable of self charge through triboelectrification effect [164].…”
Section: Organic Conductorsmentioning
confidence: 99%
“…Similarly, PPy was deposited on an elastic membrane made of PDMS fibres, obtaining a flexible strain sensor with a specific volume resistance of 448 Ω cm [162]. A more complex structure was achieved by Park et al [157] where a pressure/temperature/strain sensor and a flexible capacitor was fabricated in a single device. They used a PDMS coated microporous polypyrrole/graphene foam composite (PDMS/PPy/GF).…”
Section: Organic Conductorsmentioning
confidence: 99%
“…The current trend for those miniaturized sensing systems is to integrate with MSCs, which can avoid the external power supply, and thus, decrease the overall volume as well as weight. For this motivation, numerous studies on sensor/MSCs self‐powered systems including photodetectors, gas sensors, and strain sensors have been reported . For instance, Kim et al reported on the fabrication of flexible MSC arrays with hybrid electrodes of MWCNT/V 2 O 5 nanowire composites, which powered the SnO 2 NW UV sensor on the same substrate.…”
Section: Functionalization Of Micro‐supercapacitorsmentioning
confidence: 99%